Diagnostic Value of Serum Sodium Level and Neutrophil-to-Lymphocyte Ratio in Predicting Severity of Acute Appendicitis: A Retrospective Cross-Sectional Two-Center Study - Serdar Senol; Mustafa Kusak; Dursun Burak Özdemir; Ahmet Murat Sendil (Medicina)
Background and Objectives: The best way to distinguish complicated acute appendicitis (CAA) from uncomplicated acute appendicitis (UCAA) is still under debate. The aim of this study was to investigate the potential use of the serum sodium (Na+) level and the neutrophil-to-lymphocyte ratio (NLR) to distinguish CAA from UCAA and to evaluate whether CAA is more reliably diagnosed using these two variables together. Materials and Methods: This was a retrospective, cross-sectional, two-center study of patients diagnosed with AA between 1 January 2016 and 31 December 2023. The demographic and analytical variables were analyzed. The NLR was defined as the quotient between the absolute values of neutrophils and lymphocytes. Hyponatremia was defined as a serum Na+ level of ≤135 mmol/L. The sensitivity and specificity of the NLR and the serum Na+ level in the diagnosis of CAA were determined by assessing the receiver operating characteristic curves. Results: Among the patients who underwent an appendectomy, 3066 histologically confirmed AA cases were identified and included in this study. The registered data revealed that 348 (11.3%) patients had CAA, and the remaining 2718 (88.7%) patients had UCAA. The mean ages were 49.47 ± 18.97 and 38.16 ± 14.50, respectively (p < 0.001). The analysis revealed an exponential correlation between the NLR and the serum Na+ level with a moderate degree of agreement with CAA (Cohen’s Kappa: 0.461, p < 0.001). For CAA, using the NLR and the serum Na+ level, the areas under the curve and the cutoffs were 0.664, 4.2 with a confidence interval (CI) of 0.647–0.681 and 0.727, 135 mmol/L with a CI of 0.711–0.742, respectively; all these values were significant with a p-value of <0.001. Conclusions: Although the serum Na+ level is a more effective marker than the NLR, using these two variables together can help detect high-risk patients who may benefit from early management by limiting delays in surgery.